2009
DOI: 10.1113/jphysiol.2008.157461
|View full text |Cite
|
Sign up to set email alerts
|

Epac mediates PACAP‐dependent long‐term depression in the hippocampus

Abstract: Extensive work has shown that activation of the cAMP-dependent protein kinase A (PKA) is crucial for long-term depression (LTD) of synaptic transmission in the hippocampus, a phenomenon that is thought to be involved in memory formation. Here we studied the role of an alternative target of cAMP, the exchange protein factor directly activated by cyclic AMP (Epac). We show that pharmacological activation of Epac by the selective agonist 8-(4-chlorophenylthio)-2 -O-methyl-cAMP (8-pCPT) induces LTD in the CA1 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 57 publications
5
77
0
Order By: Relevance
“…Epac increases membrane fusion by activating Sec1/Munc13 (Kwan et al, 2007) or SNARE proteins (Sedej et al, 2005). Inhibition of trans-Golgi traffic using the bacterial toxin brefeldin A decreases the influence of Epac on synaptic transmission, suggesting that Epac isoforms activate Rab3A exocytosis in both synaptic and Golgi trafficking pathways (Ster et al, 2009). That is, Epac pathways likely activate proteins in the PKA pathway (e.g., Rab3A, mUNC proteins, SNAREs) (Hochbaum et al, 2008), but also may activate parallel (redundant) Ca 2ϩ -dependent pathways important for plasmalemmal sealing (Fig.…”
Section: Model Of Plasmalemmal Sealingmentioning
confidence: 99%
“…Epac increases membrane fusion by activating Sec1/Munc13 (Kwan et al, 2007) or SNARE proteins (Sedej et al, 2005). Inhibition of trans-Golgi traffic using the bacterial toxin brefeldin A decreases the influence of Epac on synaptic transmission, suggesting that Epac isoforms activate Rab3A exocytosis in both synaptic and Golgi trafficking pathways (Ster et al, 2009). That is, Epac pathways likely activate proteins in the PKA pathway (e.g., Rab3A, mUNC proteins, SNAREs) (Hochbaum et al, 2008), but also may activate parallel (redundant) Ca 2ϩ -dependent pathways important for plasmalemmal sealing (Fig.…”
Section: Model Of Plasmalemmal Sealingmentioning
confidence: 99%
“…An Epac-null mutation impairs long-term potentiation (LTP) that is paralleled with the severe deficits in spatial learning and social interactions (Yang et al, 2012). Epac is thought to be a key mediator in the effects of PACAP (Ster et al, 2009), a peptide that has been recently implicated in the pathophysiology of posttraumatic stress disorder (PTSD) and fear memory formation (Ressler et al, 2011). Thus, NPY may modulate a variety of behaviors, including conditioned fear (Gutman et al, 2008) and human stress reactivity (Mickey et al, 2011;Witt et al, 2011) via Epac pathways and serve as a critical element in the pathophysiology of depression, PTSD, and other neuropsychiatric disorders.…”
Section: Implications Of Epac As a Novel Intracellular Signaltransducmentioning
confidence: 99%
“…By contrast, another study showed that the application of PACAP38 enhanced AMPA-evoked currents (Michel et al, 2006). PACAP38 has been also shown to induce a form of long-term depression (LTD) in hippocampal neurons that requires interaction of AMPA receptor subunits with scaffolding proteins (Kondo et al 1997;Roberto et al 2001;Ster et al, 2009), thus validating its role in learning and memory. This has been further confirmed by the use of transgenic animals (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%